3 - An Overview of the Conditions of Workers and the Unions in South Africa and Nigeria 51 - Hlatshwayo, Mondli; Onyeonoru, Ifeanyi P. (African Sociological Review, 2022)
This paper discusses the conditions of workers and the unions in South Africa and Nigeria pointing out obstacles and challenges similar in both countries. Whilst the contexts are different, trade unions in Nigeria and South Africa had to contend with the expression of colonialism and neo-colonial oppression in the workplaces. In post-independence, Nigerian unions had to mobilise against neoliberal policies, leading to confrontation with the government of the day. Similarly, in post-apartheid South Africa, unions had to contend with workplace restructuring imposed by employers and the state. Neoliberal attacks on workers and working conditions have also led to changes in the social composition of workers and the rise of precarious forms of work in both countries. Beyond that, union federations are also faced with fragmentation and division, weakening their position to challenge attacks on workers.